Soluble transferrin receptor levels among pregnant women in Port Harcourt, Nigeria - Azubuike, Nyebuchi C.; Elechi-Amadi, Kemzi N.; Briggs, Ojoye N.; Jeremiah, Zacchaeus A. (International Journal of Research in Medical Sciences, 2019)
Background: Anaemia in pregnancy is one of the medical problems that affect pregnant women in developing countries. It contributes considerably to the morbidity and mortality in pregnancy especially in areas where malaria is endemic. The concentration of soluble transferrin receptor is a reflection of body iron status. It is therefore, a valuable tool for assessing bone marrow erythropoetic activity and can also be a marker of iron deficiency. Methods: This study evaluated the levels of soluble transferrin receptor in pregnant subjects. A total of 275 pregnant subjects of age 20 to 45 years and 88 age-matched apparently healthy control subjects were involved in this study. Individuals who had severe anaemia, HIV infection, sickle cell disease or Hookworm infestation were excluded from this study. Five millilitres (5ml) of blood were collected from each consenting subject for the analysis of soluble transferrin receptor, haematological parameters and iron parameters using appropriate methods. Results: The mean value of parameters for the study subjects were sTfR( 21.16±9.11 nmol/L), Hb(9.05±1.22 g/dl), TIBC(332.61±80.87 µg/dl), Serum Iron(97.91±39.44 µg/dl), LIBC(239.36±80.52 µg/dl), TS(30.24±11.00 %) while for control subjects were sTfR(18.21±3.77 nmol/L), Hb(12.19±0.66 g/dl), TIBC(261.94±52.49µg/dl), Serum Iron(107.10±34.77 µg/dl), LIBC(155.52±61.25 µg/dl), TS(42.81±18.03 %). The mean sTfR levels in pregnant women was significantly lower (p<0.001) than in control subjects. The pregnant women also had significantly lower values of Hb (p<0.001), serum iron (p=0.038) and TS( p<0.001) values, and significantly higher values of TIBC(p<0.0001) and LIBC(p<0.0001). There were also increases in soluble transferrin receptor levels from first to third trimesters. The sensitivity of sTfR as against Serum iron parameters from this study was 76% while the specificity was 50%. The positive predictive value was 60% while the negative predictive value was 50%. Conclusions: sTfR may be a useful supplementary diagnostic tool in the management of anaemia in pregnancy.